Penguatan Pelatihan Penyelenggaraan Jenazah Berdasarkan Pedoman Tarjih Muhammadiyah pada Majelis Taklim Nurul Qalbi Kelurahan Pengkase Oeleta Kecamatan Alak Kota Kupang: Strengthening Training on Funeral Management Based on Muhammadiyah Tarjih Guidelines at the Nurul Qalbi Taklim Assembly, Penkase Oeleta Village, Alak District, Kupang City - Syarifuddin Darajad; Ihwan Ihwan; Yahya Nikmad Nobisa; Siti Syahida Nurani; Wahid Hasym TRA Beni; Kamis Karno; Andi Irfan; Marwan Gozali; Siti Hajar; Darma Nobisa; Arifin Arifin; Masita Bareut (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This Community Service Program (PKM) for funeral arrangements was conducted by the Muhammadiyah University of Kupang Community Service Team at the Nurul Qalbi Taklim Assembly, Alak District, Kupang City. This training provided members of the Taklim Assembly with insight into funeral arrangements according to the Sunnah of the Prophet Muhammad, supported by the Tarjih Muhammadiyah guidelines. The methods used in this training were lectures, practice of funeral arrangements, and videos of funeral arrangements by Tarjih Muhammadiyah. This training activity had a positive impact on the knowledge and experience of the Taklim Assembly members regarding funeral arrangements, in line with the demands of the Prophet Muhammad SAW, as outlined in the Tarjih Muhammadiyah decision. Overall, this funeral arrangement training activity was deemed successful against the planned target. The activity had 20 participants out of a total of 30 members of the Taklim Assembly; this demonstrates motivation and enthusiasm to understand the material presented. Participants followed the training activities well, the stages of the funeral arrangement training from beginning to end.